Pemikiran Pendidikan Naquib al-Attas Dalam Pendidikan Islam Kontemporer - Sapri; Zaini Dahlan; Ahmad Tarmizi Hasibuan; Ely Rahmawati (TADRIS: Jurnal Pendidikan Islam, 2022)
Islamic education as one of the recognized scientific disciplines and has attracted the interest of the participants, especially for students who want to study it seriously. However, this field of study and discipline is not fast enough in its development, when compared to the number of other fields of Islamic studies. Even so, the portrait of Islamic education can actually be described in various perspectives. For example, from the educational perspective of Naquib al-Attas. This study aims to explore the educational concept of Naquib Al Attas in terms of the meaning and purpose of education, curriculum and educational methods as well as the authority and role of the teacher. The research uses a descriptive approach. This is done to be able to reveal the concept of education in Naquib Al Attas' thought based on reading related books and articles. The results of this study indicate that the thoughts of Naquib Al Attas tend to be selectively reconstructive which seeks to present an integrated Islamic education system. While in the Al Attas Curriculum seeks to integrate Science (Fardhu Ain and Fardu Kifayah), so the method used is the cultivation of Adab (Faith-Science-Charity).